Mobility and Distribution - Kearl, James R.; Pope, Clayne L. (The Review of Economics and Statistics, 1984)
This article examines the mobility of Utah households as measured by their wealth holdings reported in the census manuscripts of 1860 and 1870. Substantial mobility is observed though there is a tendency for the households to remain in the richest decile. Control for age, nativity, or dichotomies such as urban-rural or farm and nonfarm does not substantially reduce mobility. The lack of association of characteristics with the observed mobility, combined with high levels of cross-sectional inequality, highlights the importance of measuring mobility as well as wealth or income dispersion in order to make valid normative inferences. S UBSTANTIAL effort has been devoted to analyses of distributional inequality, whether measured by individual incomes, earnings, or wealth holdings. As a consequence, we know a good deal about dispersion at various points in time for measures of economic position and hence about the changes in dispersion across decades and even centuries: income, earnings and wealth distributions evidence considerable dispersion and the dispersion appears to have narrowed somewhat in the twentieth century after earlier increases in inequality. However, the small changes happen slowly so that the stability of measured dispersion over decade or longer intervals is remarkable (Williamson and Lindert, 1980). We know a good deal less about economic mobility-the movement of individual households through these disperse distributions (cf. McCall, 1973, or Schiller, 1976). This paper considers evidence of mobility for a panel of households with a relatively stable distribution through time sampled from an economy with increasing inequality in wealth holdings. We find substantial mobility over a two-decade interval. Mobility of the sort we observe poses some difficulties for normative judgments when distributional dispersion is an element in welfare evaluations of a society or of policies likely to have distributional impacts. We return to this issue briefly in a concluding section. I. The Distribution of Wealth in Utah,